Analisis Standar Pengelolaan Pendidikan Anak Sekolah Dasar di Pendidikan Guru Sekolah Dasar Universitas Pahlawan Tuanku Tambusai - Kusuma, Yanti Yandri; Sumianto, Sumianto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to determine how the Standards for Management of Elementary School Children's Education. This research was conducted on elementary school teacher education students at the Hero University Tuanku Tambusai for the 2020/2021 academic year. The research method used in this study is a quantitative and qualitative approach, survey methods with measurement techniques, whilethe research data collected were analyzed using descriptive statistical analysis techniques, ProductMoment correlation, and simple regression. The population using the target population is all students in the fifth semester of PGSD study program at the Hero University Tuanku Tambusai totaling 29 students. Sampling was carried out using the total sampling technique (total sampling).